BUSINESS PROPOSAL 24 HOURS CHILDCARE & DEVELOPMENT CENTRE - Lee, GimTee (2006)
The purpose of this dissertation was to determine the feasibility of operating a Childcare development centre to serve children from eighteen months to 12 years of age. In order to ensure the success of operating the Childcare Development Centre in Singapore, a comprehensive business plan needed to be developed. Beside gaining confidence, getting financial support and also seek the approval from the Ministry of Community Development Youth and Sport for operating the Childcare Development Centre. SingaporeÃÂÃÂ¢ÃÂÃÂÃÂÃÂs child population has being falling over the years, but the demand for childcare continues to increase as more mother of young children go out to work. SingaporeÃÂÃÂ¢ÃÂÃÂÃÂÃÂs PM Lee maiden National Day Rally speech in August 2004 was indicated to have more incentives to help Singaporean to have more babies. The childcare market is expected to increase in demand towards the end of 2006 with an increase of 11.2% over the 5-year period from 2007 to 2012. To exploit the business plan, many steps are to be accomplished. Review of the relevant literature to identify issues, trends, consumer behaviour, and competitors within the industry need to be made. Once the business plan was completed, a final analysis had to be accomplished to determine whether the opening of the Childcare Development Centre would be profitable besides serving the community.